2011
DOI: 10.1007/s00229-011-0429-x
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Green operators for quantum mechanical Hamiltonians. I. The hydrogen atom

Abstract: We study a new approach to determine the asymptotic behaviour of quantum many-particle systems near coalescence points of particles which interact via singular Coulomb potentials. This problem is of fundamental interest in electronic structure theory in order to establish accurate and efficient models for numerical simulations. Within our approach, coalescence points of particles are treated as embedded geometric singularities in the configuration space of electrons. Based on a general singular pseudo-differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Remark 6.23. It is important to notice that finding good compactifications of X related to the N -body problem is useful for the problem of approximating numerically the eigenvalues and eigenfunctions of N -body Hamiltonians [1,16,17,18,19,50]. In particular, this gives a further justification for trying to find the structure of the character space of E(X).…”
Section: )mentioning
confidence: 99%
“…Remark 6.23. It is important to notice that finding good compactifications of X related to the N -body problem is useful for the problem of approximating numerically the eigenvalues and eigenfunctions of N -body Hamiltonians [1,16,17,18,19,50]. In particular, this gives a further justification for trying to find the structure of the character space of E(X).…”
Section: )mentioning
confidence: 99%
“…[47,Theorem 6.8.1]) that u is analytic on R 3N \ S. In this case a strong local regularity result was obtained in [24] in the neighborhood of the simple coalescence points, where it was shown that locally u(x) = u 1 (x) + |l(x)|u 2 (x) with u 1 and u 2 real analytic and l linear. See also [8,10,11,16,20,22,21,23,25,36,38,51,54,55,56] and references therein for more results on the regularity of the eigenfunctions of Schrödinger operators. Related is [19] which was circulated after this article has been submitted.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea is to construct an asymptotic parametrix for a Hamiltonian which encodes all the required asymptotic information. Details concerning the general concept of an asymptotic parametrix has been presented elsewhere [11], and a first application to the Hamiltonian of the hydrogen atom was given in [9]. In the present work, we want to establish an explicit construction of an asymptotic local parametrix for the Hamiltonian of two-electron systems, in particular the helium series and hydrogen molecule, near coalescence points of two particles, i.e., two electrons or an electron and a nucleus.…”
Section: Singular Analysis Meets Quantum Chemistrymentioning
confidence: 99%